Noncoded amino acids in protein engineering: Structure–activity relationship studies of hirudin–thrombin interaction. (16th January 2018) - De Filippis, Vincenzo; Acquasaliente, Laura; Pontarollo, Giulia; Peterle, Daniele
Abstract: The advent of recombinant DNA technology allowed to site‐specifically insert, delete, or mutate almost any amino acid in a given protein, significantly improving our knowledge of protein structure, stability, and function. Nevertheless, a quantitative description of the physical and chemical basis that makes a polypeptide chain to efficiently fold into a stable and functionally active conformation is still elusive. This mainly originates from the fact that nature combined, in a yet unknown manner, different properties (i.e., hydrophobicity, conformational propensity, polarizability, and hydrogen bonding capability) into the 20 standard natural amino acids, thus making difficult, if not impossible, to univocally relate the change in protein stability or function to the alteration of physicochemical properties caused by amino acid exchange(s). In this view, incorporation of noncoded amino acids with tailored side chains, allowing to finely tune the structure at a protein site, would facilitate to dissect the effects of a given mutation in terms of one or a few physicochemical properties, thus much expanding the scope of physical organic chemistry in the study of proteins. In this review, relevant applications from our laboratory will be presented on the use of noncoded amino acids in structure–activity relationships studies of hirudin binding to thrombin.